THE COMPARASION OF PR AND SM CODOPANT FOR IMPROVING IONIC CONDUCTIVITY OF SOLID ELECTROLYTE GADOLINIUM DOPED CERIA (GDC) AS IT-SOFC APPLICATION : COMPREHENSIVE REVIEW - Faisal Akbar, Muhammad
Currently, many countries still rely on fossil fuels such as petroleum and coal for energy sources. The dependency on fossil fuels as a source of energy results in various environmental and health problems. Therefore, many renewable energy sources are being developed at this time. For example, one of a renewable energy source is a fuel cell. Solid Oxide Fuel Cell (SOFC) is a type of fuel cell that uses solid oxide material. SOFC is an electrochemical device that can convert chemical energy from fuel into electrical energy by utilizing oxygen and hydrogen for reaction. The main problem with SOFCs is the high operating temperature (~ 1000oC). Electrolyte material which has high ionic conductivity is one of many solutions in material selection to reduce the operating temperature of SOFC. Gadolinium Doped Ceria (GDC) is one of the ceria-based materials which can be used for intermediate-temperature SOFC. For reducing the operating temperature, it is necessary to add a co-doping to the solid electrolyte of GDC in order to have high ionic conductivity and stability at medium operating temperature. The aim of this study is to compare the effects of co-doping Praseodymium (Pr) and Samarium (Sm) on the physical and electrical characteristics of GDC solid electrolytes for material applications at the Intermediate Temperature SOFC (ITSOFC). The method used in this study is literature study. This study will compare the effects of two co-dopings on the ionic conductivity values and also the value of its activation energy. From the literature study, the results show that the addition of Pr and Sm codoping will affect the lattice parameters, microstructure, ionic conductivity and activation energy of solid electrolyte GDC. Addition of co-doping Pr and Sm will increase the lattice parameters of the cubic fluorite structure. The microstructure formed shows a small grain size and homogeneous which indicates that the solid electrolyte GDC with co-doping Pr and Sm have good mechanical and electrical properties. The ionic conductivity increases with the addition of the co-doping Pr concentration up to 6% and then decreases with the increasing concentration of Pr at 500 oC operating temperature. For the co-doping effect of Sm, the ionic conductivity increases up to 5% Sm concentration and then decreases with the increasing concentration of Sm at 700oC operating temperature. Activation energy decreased at the optimum co-doping concentration of Pr and Sm. Overall, the use of Pr co-doping is the most effective at increasing the ionic conductivity and decreasing the activation energy at lower operating temperatures.